Odor symptom management in patients with malignant wounds in Mali: the use of a cinnamon dressing - Charlotte Ngô; Fatoumata M Sidibe; Sophie Goossens; Dianeko Zenabou Tapa; Irène Kriegel; Abdramane A Kone; Moussa Bathily; Hamidou D Doumbia; Claire Rieux; Isabelle Fromantin (BMC Cancer)
Abstract Background In Mali, cancer patients are often diagnosed at stage III or IV. Tumor wounds are more frequent and associated with malodorous exudates, responsible for an altered quality of life and stigmatization of patients. Cinesteam® Cinnamon Dressing is an adsorbent dressing designed to reduce odors. This study aimed at demonstrating the feasibility of routine use of cinnamon dressing in the Malian context, and to assess its effect on tumor wound odors. Patients and methods This is a prospective observational pilot study conducted jointly by the oncology department of the Point G University hospital in Bamako and Médecins Sans Frontières France. Included patients suffered from a malignant malodourous wound and were treated with cinnamon dressing. The primary endpoint was wound odor. Secondary endpoints were appetite, duration of dressing efficacy and ease of use. Results Forty patients were included in this pilot study. Complete data and follow-up were available for 19 patients only. The odor score reported by patients was significantly decreased after 10 days of cinnamon dressing (odor score 1.7 versus 3.3, t-test 0.00003). Seventeen patients reported that the CINESTEAM® dressing was easy to use, even for patients receiving home-based palliative care in remote areas. The dressing provided an odor control that lasted more than 24 h. One year after inclusion, more than half of the patients had died of their cancer, indicating a very advanced stage at diagnosis. The cinnamon dressing had no effect on appetite, but most of the patients were undergoing palliative chemotherapy, which may account for this result. Conclusion The use of innovative dressings is feasible, even in very deprived contexts, and might decrease the discomfort linked with unpleasant odors in tumoral wounds. Odor management is crucial to restore self-esteem and to prevent patients’ stigma and isolation.